2023
DOI: 10.1093/nsr/nwad039
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradable polar-functionalized polyethylenes

Abstract: The degradation of plastics has attracted much attention from the global community. Polyethylenes (PEs) as the most abundant synthetic plastics are mostly studied. PE is non-degradable and non-polar because of the sole presence of the pure hydrocarbon components. Concurrent incorporation of both in-chain cleavable and functional groups into the PE chain is an effective pathway to overcome the non-degradable and non-polar issue; however, the method for achieving this pathway remains elusive. Here, we report the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
0
18
1
Order By: Relevance
“…ATR-IR analyses were performed for representative ethylene and 2,7-octadienyl ether copolymers, and a polyethylene sample produced by Pd-3 [ 46 ] was also tested as a comparison ( Figure 3 ). As shown in Figure 3 , all the copolymers feature characteristic bands at close 968 cm −1 , assigned to the symmetric C–O–C stretching vibration of the allyl ether unit, which is absent in the PE sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ATR-IR analyses were performed for representative ethylene and 2,7-octadienyl ether copolymers, and a polyethylene sample produced by Pd-3 [ 46 ] was also tested as a comparison ( Figure 3 ). As shown in Figure 3 , all the copolymers feature characteristic bands at close 968 cm −1 , assigned to the symmetric C–O–C stretching vibration of the allyl ether unit, which is absent in the PE sample.…”
Section: Resultsmentioning
confidence: 99%
“…Materials: furfuryl alcohol, tetrahydrofurfuryl alcohol, and solketal were commercially available, which were further dried over Na 2 SO 4 and NaHCO 3 for 2 h and distilled. Palladium catalysts Pd-1 , Pd-2, and Pd-3 were prepared using the literature procedures [ 44 , 45 , 46 ]. All other reagents were commercially available and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…Due to formation of a strong chelate after CO insertions, these copolymerizations inevitably furnish a mixture of isolated and alternating carbonyl units in the presence of excess CO. [21] Compared to that of alternating carbonyl units, in-chain isolated carbonyls may maximize the breakdown of the polymer chains into smaller pieces during photodegradation. [22] In 2021, Nozaki et al reported the synthesis of nonalternating polyketones with excellent isolated carbonyl insertion selectivity from ethylene and metal carbonyls. [23] Inspired by the significant progress made in CO/ethylene copolymerization, we report herein a new copolymerization protocol to prepare polyethylenes with low content isolated carbonyls from CO2 and ethylene.…”
Section: Figure 1 Copolymer Synthesis From Co2 and Ethylenementioning
confidence: 99%
“…[1][2][3][4] Since Brookhart et al discovered nickel(II) and palladium(II) catalysts supported by α-diimine ligands, 5,6 late transition metal catalysts have received tremendous attention over the past 30 years and have been proved to be very versatile in accessing diverse polyolefins. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In contrast to extensive studies on cationic α-diimine nickel (II) catalysts with the activation of co-catalysts, another milestone in catalyst studies, neutral salicylaldiminato nickel(II) catalysts, discovered by Johnson et al 27 and Grubbs et al, 28,29 have better tolerance toward polar media but have attracted much less attention in terms of the production of diverse polyolefins. Unlike the α-diimine nickel(II) catalysts, the active center of this type of catalyst is electrically neutral, and thus it allows ethylene polymerization without the help of Lewisacidic co-catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…1–4 Since Brookhart et al discovered nickel( ii ) and palladium( ii ) catalysts supported by α-diimine ligands, 5,6 late transition metal catalysts have received tremendous attention over the past 30 years and have been proved to be very versatile in accessing diverse polyolefins. 7–26…”
Section: Introductionmentioning
confidence: 99%